Different Learning Style, Different Performance in TOEFL Reading: Is That Right? - Elisa Ratih; Khilda Husnia Abidah (English Learning Innovation (englie), 2022)
This present study has aim to answer a question “is there any relationship between students’ learning styles in TOEFL reading comprehension test?”. Therefore, this study was done for knowing whether there is a significant relationship between students’ learning styles in reading comprehension performance on the TOEFL test or not. The University of Islam Malang was chosen as the place to conduct this study with 37 students in the fourth semester of English Department. A questionnaire and TOEFL reading test were used as the instruments in this study to find the result. Both of the instruments were done in 45 minutes. Based on the results that were counted statistically using SPSS, the findings showed that the score of visual (M = 43,22), kinesthetic (M = 38,70), and auditory (M = 35,00) for reading achievement. Moreover, it also showed that df = 2, F = 1.102, P = .344. The results informed that there is no significant difference between students’ learning style in TOEFL reading comprehension performance. Due to limitations that exist in this quantitative study, future researchers are suggested to do research which broader population involvement and include reading strategies to give more insightful results regarding reading comprehension that might be useful for the learning process.